TINDAK PIDANA PERUSAKAN LINGKUNGAN HIDUP DALAM PERSPEKTIF HUKUM ISLAM - Asy'ari Asy'ari; Edwar Ibrahim; Aris Nandar (Kalam: Jurnal Agama dan Sosial Humaniora, 2023)
The environment functions as a dynamic living system replete with diverse natural resources essential for sustaining all forms of life. The collective obligation to safeguard this environment stems from the anticipation of enduring advantages. Environmental degradation, conversely, represents a condemnable transgression, inflicting severe detriment upon the vitality of organisms inhabiting our planet's surface. This research endeavors to elucidate the ramifications of environmental degradation while considering Islamic legal viewpoints on the matter. Employing qualitative research techniques within a normative framework, this study references various scholarly works, encompassing books, journals, and scientific manuscripts. The study's findings can be summarized as follows: firstly, environmental degradation yields consequences such as soil infertility, dwindling water reservoirs, loss of biodiversity, and the resultant occurrences of floods, landslides, and global warming. Secondly, from an Islamic jurisprudential perspective, environmental degradation qualifies as a criminal act. Within Islamic law, wrongdoing, or "jarimah," pertains to actions, either active or passive, capable of undermining societal order, personal beliefs, individual livelihoods, property rights, and honor. Environmental degradation contravenes the law, leading to punitive measures aimed at deterrence. It is worth noting that environmental destruction lacks explicit legal provisions (nash) but falls into the category of "jarimah ta’zir," allowing discretionary penalties to be imposed.